Engineering Fe–Fe3C@Fe–N–C Active Sites and Hybrid Structures from Dual Metal–Organic Frameworks for Oxygen Reduction Reaction in H2–O2 Fuel Cell and Li–O2 Battery. (8th April 2019) - Wang, Hao; Yin, Feng‐Xiang; Liu, Ning; Kou, Rong‐Hui; He, Xiao‐Bo; Sun, Cheng‐Jun; Chen, Biao‐Hua; Liu, Di‐Jia; Yin, Hua‐Qiang
Abstract: Dual metal–organic frameworks (MOFs, i.e., MIL‐100(Fe) and ZIF‐8) are thermally converted into Fe–Fe3 C‐embedded Fe–N‐codoped carbon as platinum group metal (PGM)‐free oxygen reduction reaction (ORR) electrocatalysts. Pyrolysis enables imidazolate in ZIF‐8 rearranged into highly N‐doped carbon, while Fe from MIL‐100(Fe) into N‐ligated atomic sites concurrently with a few Fe–Fe3 C nanoparticles. Upon precise control of MOF compositions, the optimal catalyst is highly active for the ORR in half‐cells (0.88 V in base and 0.79 V versus RHE in acid in half‐wave potential), a proton exchange membrane fuel cell (0.76 W cm −2 in peak power density) and an aprotic Li–O2 battery (8749 mAh g −1 in discharge capacity), representing a state‐of‐the‐art PGM‐free ORR catalyst. In the material, amorphous carbon with partial graphitization ensures high active site exposure and fast charge transfer simultaneously. Macropores facilitate mass transport to the catalyst surface, followed by oxygen penetration in micropores to reach the infiltrated active sites. Further modeling simulations shed light on the true Fe–Fe3 C contribution to the catalyst performance, suggesting Fe3 C enhances oxygen affinity, while metallic Fe promotes *OH desorption as the rate‐determining step at the nearby Fe–N–C sites. These findings demonstrate MOFs as model system for rational design of electrocatalyst for energy‐based functional applications. Abstract : An Fe–N–C catalyst is derived from dual metal–organic frameworks through facile pyrolysis, affording excellent oxygen reduction catalytic performance in alkaline/acidic half‐cells, a H2 –O2 proton exchange membrane fuel cell, and a Li–O2 battery. The excellent catalytic performance benefits from density populated Fe–Fe3 C@Fe–N–C dual active sites, hierarchical porosities for mass transport, and partial carbon graphitization for charge transfer.